Characterization of fatigue properties of bonded-in pultruded rod timber connection / Zakiah Ahmad and Adiza Jamadin - Ahmad, Zakiah; Jamadin, Adiza (Research Management Institute (RMI), 2013)
Timber is one of the oldest construction materials used by mankind, due to it being a readily available natural resource. Timber has many advantages over other commonly used building material (such as steel and concrete) including its availability, workability, strength to weight ratio, renewable resources and very importantly its low impact on the environment. By adopting the timber as the construction material or structural members, timber needed to be connected or to become longer or jointed to other members. Due to structural application, timber must go through proper jointing or connecting process. Not like as the steel or concrete structure, it can be welded or re-fabricate to connect each members. The traditional timber connection systems based on fasteners such as nails, bolts, screws and dowels, may not be preferred choice of systems for heavy timber structures because of some disadvantages associated, e.g. long manufacturing times, high labour cost, heavy joints and corrosion problems (Mehrab and Martin, 2003). New types of timber connections such as glued-in bolts or rod and bonded-in connection have been introduced to remove some disadvantages of traditional joints. This study focused only on bonded-in timber connection system into the selected timber species…